Caracterização em tempo real da birrefringência de forma do sistema PS/PP por técnica reo-óptica - Vasconcelos, Rayana Larissa (Universidade Federal de São Carlos, 2019)
The rheo-optical behavior of polystyrene (PS), polypropylene (PP) and immiscible dilute mixtures of these polymers was studied in order to determine the flow birefringence and form birefringence of these materials. The transmitted light intensity between cross-polarizers (IN) was measured using an optical system composed of a polarized light optical microscope, a system that controls the shear and heating, and an optical detector with photoresistors. These measurements allowed to calculate the optical path difference and birefringence for each polymeric system. The IN was considerably higher for pure PS than for pure PP, due to the greater polarizability of the aromatic rings of the PS in comparison to the olefinic groups of the PP. The addition of a PP dispersed phase in the PS matrix caused a shift of the IN curve for higher shear rates, indicating a decrease in the total birefringence of the mixtures relative to the pure matrix. Conversely, the addition of a PS dispersed phase in the PP matrix generated a shift of the IN curve for lower shear rates, because there was an increase in the total birefringence of the mixtures in relation to the pure matrix. These opposite displacements agree with the additive effect of the flow birefringence of each matrix, being negative for PS and positive for PP, and of the form birefringence, always positive. Nevertheless, the form birefringence did not show a dependence of the concentration of the dispersed phase as expected.
Real time characterization of form birefringence of PS/PP system by rheo-optical technique
Keywords: Birrefringência de fluxo; Birrefringência de forma; Caracterização reo-óptica; Poliestireno; Polipropileno; Flow birefringence; Form birefringence; Rheo-optical characterization; Polystyrene; Polypropylene; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS